Prototype of IoT Application for Monitoring Street Lighting by Utilizing Solar Power - Atmojo, Fattah Satrio; Nurchim; Pramono (Universitas Nusantara PGRI Kediri, 2025)
Street lighting plays a vital role in ensuring the safety and comfort of road users, especially at night. Manual monitoring of streetlights is considered inefficient as it requires significant time and effort. This study proposes an automatic monitoring system based on the Internet of Things (IoT) to enhance the effectiveness of streetlight supervision. The system is built using an ESP32 microcontroller integrated with a current sensor, voltage sensor, and light sensor (LDR). The device connects to the internet and transmits data in real-time to a cloud-based platform, where it is visualized on a monitoring dashboard. Test results show that the system can accurately detect the on/off status of the lights, with LDR readings ranging from 0 to 4045, current sensor showing 0.2 amperes, and voltage sensor recording 7.4 volts. Additionally, the system can automatically control the relay to switch the lights on or off based on sensor input. Overall, the proposed system improves the efficiency of monitoring, enables faster detection of lighting conditions, and supports more timely and energy-efficient maintenance of street lighting infrastructure